2003
DOI: 10.1016/s0741-5214(03)00920-0
|View full text |Cite
|
Sign up to set email alerts
|

Microthrombectomy reduces postsclerotherapy pigmentation: multicenter randomized trial

Abstract: In veins 1 mm or smaller, microthrombectomy reduced pigmentation and improved overall clinical results. In veins 3 mm or smaller, statistical significance was not achieved, but thrombectomy resulted in faster resolution of the postsclerotherapy pain and inflammation. On the basis of these results, microthrombectomy after sclerotherapy is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 22 publications
0
26
0
5
Order By: Relevance
“…A randomized multicenter study found that microthrombectomy 1 to 3 weeks after the injection of small varicose veins (Յ1 mm) resulted in less hyperpigmentation, and in varicose veins up to 3 mm, it resulted in less pain and inflammation. 71 …”
Section: Interventional Treatmentmentioning
confidence: 99%
“…A randomized multicenter study found that microthrombectomy 1 to 3 weeks after the injection of small varicose veins (Յ1 mm) resulted in less hyperpigmentation, and in varicose veins up to 3 mm, it resulted in less pain and inflammation. 71 …”
Section: Interventional Treatmentmentioning
confidence: 99%
“…Hyperpigmentation may occur from heme trapped with the sclerosed superficial veins. Phlebectomy of the affected vein can be used to minimize this side effect (31).…”
Section: Usgsmentioning
confidence: 99%
“…Dies entspricht nicht mehr dem physiologischen Hautbild. Die Haut wird anfäl-liger gegenüber UV-Schäden und es besteht -gerade bei dunkleren Hauttypenzusätzlich eine erhöhte Gefahr postoperativer Pigmentverschiebungen [23].…”
Section: » Nach Dermabrasivenunclassified